Environment-friendly cat litter and manufacturing method and application thereof

CN122997038APending Publication Date: 2026-10-30HUNAN DONGFANGHONG PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610868602.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

当前市售主流猫砂主要分为矿物型猫砂与植物基猫砂两类,二者均存在难以兼顾性能、成本与环保的技术瓶颈

Benefits of technology

1)本发明提供一种环保型猫砂及其制造方法、应用,以天然谷壳为原料,通过三重协同改性处理,实现猫砂吸水、除臭、降尘性能和结团强度的同步提升,降低了生产成本,不仅使用过程中不易破碎,清理便捷,更可生物降解,符合环保要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides an environment-friendly cat litter and a manufacturing method and application thereof, comprising the following steps: taking natural grain shell biomass as raw material, and performing triple synergistic modification through surface delamination activation, functional group modification and multi-stage pore structure construction; the triple synergistic modification process comprises the following steps: removing the wax layer and the siliceous layer on the surface of the natural grain shell biomass, exposing the hydroxyl groups on the cellulose and the lignin, and obtaining delamination activated grain shells; converting the hydroxyl groups of the delamination activated grain shells into one or more of carboxyl groups and amine groups at least partially, and obtaining functional group modified grain shells; constructing a micropore-mesopore composite structure through temperature control carbonization of the functional group modified grain shells, and obtaining modified grain shells; and taking the natural grain shells as raw material, and realizing synchronous improvement of water absorption, deodorization, dust reduction performance and clumping strength of the cat litter through the triple synergistic modification treatment, so that the production cost is reduced, the cat litter is not easy to break in the use process, cleaning is convenient, the cat litter is biodegradable, and the environment-friendly requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cat litter technology, and in particular to an environmentally friendly cat litter, its manufacturing method, and its application. Background Technology

[0002] With the rapid development of the pet economy and the widespread adoption of pet ownership, cat litter has become an essential consumable in the pet cleaning industry. The market has placed comprehensive demands on cat litter's absorbency, clumping ability, odor control, low dust content, environmental friendliness, and cost-effectiveness. Currently, the mainstream cat litters on the market are mainly divided into two categories: mineral-based cat litter and plant-based cat litter. Both of these face technical bottlenecks that make it difficult to balance performance, cost, and environmental protection.

[0003] Mineral-based cat litter, represented by bentonite, has good water absorption and clumping properties, but the mining of raw materials damages the ecology, the dust generated during use can easily cause respiratory discomfort to pets and users, and it is difficult to biodegrade after disposal, resulting in cumulative environmental pollution.

[0004] Existing plant-based cat litter mostly uses soybean residue, corn cob, cassava flour, etc. as raw materials. Although they are biodegradable and more environmentally friendly, they generally have defects such as low water absorption efficiency, poor clumping strength, easy breakage and scattering, weak deodorization effect, and poor dust control. Cat litter made directly from natural rice husks has the disadvantages of slow water absorption, poor adsorption, weak clumping, and easy pulverization due to the dense and hydrophobic surface of rice husks, underdeveloped pore structure, and insufficient surface activity and functional groups, making it difficult to meet the needs of use.

[0005] To improve performance, existing technologies often add adhesives, chemical adsorbents, and synthetic polymers, but this increases production costs, introduces non-environmentally friendly components, reduces biodegradability, and makes it difficult to simultaneously improve water absorption, deodorization, dust reduction, and clumping strength. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide an environmentally friendly cat litter, its manufacturing method, and its application. Using natural rice husks as raw material, the invention employs a triple synergistic modification process to simultaneously improve the cat litter's water absorption, deodorization, dust reduction, and clumping strength, thereby reducing production costs. This not only makes the cat litter less prone to breakage during use and easier to clean, but also allows it to be biodegradable, meeting environmental protection requirements.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: On one hand, the present invention provides a method for manufacturing environmentally friendly cat litter, comprising: The material is prepared by a triple synergistic modification process using natural rice husk biomass as raw material, including surface delamination activation, functional group modification, and multi-level porous structure construction. The triple synergistic modification process includes the following steps: S1 Surface Delamination and Activation: Remove the waxy and silica layers from the surface of natural rice husk biomass to expose the hydroxyl groups on cellulose and lignin, thus obtaining delamination and activated rice husks; S2 functional group modification: at least part of the hydroxyl groups of the delayered activated rice husk are converted into one or more of carboxyl and amino groups to obtain functional group modified rice husks; S3 Multi-level Porous Structure Construction: Modified rice husks were constructed by temperature-controlled carbonization to create a microporous-mesoporous composite structure.

[0008] The purpose of this invention is to provide an environmentally friendly cat litter and its manufacturing method and application. Using natural rice husks as raw materials, the invention achieves simultaneous improvement in the cat litter's water absorption, deodorization, dust reduction, and clumping strength through a triple synergistic modification process. This reduces production costs and makes the cat litter less prone to breakage during use, easier to clean, and biodegradable, thus meeting environmental protection requirements.

[0009] In some embodiments, step S1 includes the following steps: S101 Take natural rice husk biomass, add an alkaline solution with a mass fraction of 5-10%, the material-to-liquid ratio is 1:8-12 (g / mL), heat to 70-90℃ and stir for 1.5-2.5 hours; After the S102 reaction is complete, the solution is repeatedly filtered and washed with deionized water until the pH of the filtrate is 6.5–7.5. S103 The washed product is placed in a ball mill and ball-milled at a speed of 180-220 r / min for 20-40 min, and then dried until the moisture content is ≤8% to obtain de-layered activated rice husk.

[0010] In some embodiments, the alkaline solution is either a sodium hydroxide solution or a potassium hydroxide solution.

[0011] In some embodiments, step S2 includes the following steps: S201 involves adding de-layered and activated rice husks to a 3-6% hydrogen peroxide solution at a material-to-liquid ratio of 1:4-6 (g / mL), heating to 65-75℃ for 1-2 hours of oxidation reaction, with continuous stirring during the process to introduce carboxyl groups. After S202 oxidation is completed, filter and dry the product, then add 2-4% ethylenediamine solution at a material-to-liquid ratio of 1:2-4 (g / mL), heat to 75-85℃ and react for 0.5-1.5 h to introduce amine groups; After the S203 reaction is completed, filter the mixture, wash it 2-3 times with anhydrous ethanol, and dry it until the moisture content is ≤8% to obtain functional group modified rice husk.

[0012] In some embodiments, the molar concentration of the carboxyl group introduced in step S201 is 1.5~2.5 mmol / g; The molar concentration of the amine group introduced in step S202 is 1.0~2.0 mmol / g.

[0013] In some embodiments, step S3, the temperature-controlled carbonization includes the following steps: The functional group-modified rice husks were placed in an inert gas atmosphere and heated to 200-600℃ at a heating rate of 4-6℃ / min, and carbonized at a constant temperature for 1-2 hours to obtain modified rice husks with a microporous-mesoporous composite structure; the inert gas was either nitrogen or argon.

[0014] In some embodiments, the method for manufacturing the environmentally friendly cat litter further includes step S4 molding process: after crushing and screening the modified rice husks, the mixture is pressed into shape to obtain the finished environmentally friendly cat litter. In step S4, the particle size of the modified rice husk after crushing and sieving is 1.5~3.0mm, the pressing pressure is 1.5~2.5MPa, and the molding time is 8~12s.

[0015] In some embodiments, the natural grain husk biomass includes any one or more of rice husks, wheat husks, sorghum husks, and millet husks.

[0016] On the other hand, the present invention provides an environmentally friendly cat litter, which is manufactured according to the manufacturing method of environmentally friendly cat litter as described in any of the preceding claims, wherein the environmentally friendly cat litter has a microporous-mesoporous composite structure and a specific surface area ≥173m² / g.

[0017] In another aspect, the present invention provides an application of the environmentally friendly cat litter as described in any of the preceding claims in the treatment of feline excrement.

[0018] This invention provides an environmentally friendly cat litter, its manufacturing method, and its application, which have the following beneficial effects: 1) This invention provides an environmentally friendly cat litter and its manufacturing method and application. Using natural rice husks as raw materials, through triple synergistic modification treatment, the cat litter's water absorption, deodorization, dust reduction performance and clumping strength are simultaneously improved, reducing production costs. It is not only not easy to break during use and easy to clean, but also biodegradable and meets environmental protection requirements.

[0019] 2) This invention provides an environmentally friendly cat litter, its manufacturing method, and its application. This application establishes a synergistic foundation through surface delamination and activation as a prerequisite for triple modification, effectively stripping the waxy and silica layers from the surface of the rice husk. On the one hand, it directly removes the main source of dust generation, reducing the dust content of the cat litter to 0.11~0.15% (data from Examples 1-3), which is far below the industry control requirement (≤0.3%), and is also significantly better than Comparative Example 2 (0.52%) which only underwent surface delamination and activation, and Comparative Example 4 (0.52%) which was directly modified without delamination. 85%) and commercially available cat litter (Comparative Example 5: 1.50%, Comparative Example 6: 0.78%); on the other hand, it exposes the hydroxyl groups on cellulose and lignin, providing sufficient active sites for subsequent functional group modification, breaking the inherent defect of hydrophobicity of natural husk. Without this step, functional group modification cannot be fully carried out. For example, the unmodified Comparative Example 1 can only introduce a small amount of active groups, resulting in extremely poor subsequent water absorption and deodorization performance (water absorption ratio of only 2.2, ammonia removal rate of 33.2%), thus opening up the core channel for improving water absorption and deodorization performance; This application achieves functional upgrades through functional group modification, forming a synergy with delamination activation: Based on the hydroxyl groups exposed after delamination activation, strong hydrophilic functional groups such as carboxyl and amine groups are introduced through a two-step oxidation-amine reaction, forming a "barrier removal-empowerment" synergy with the delamination activation step, specifically improving the water absorption and deodorization performance of cat litter. Experimental data show that, through this synergistic effect, the water absorption ratio of Examples 1-3 can reach 5.5-5.8, and the ammonia removal rate can reach 98.2-98.8%, which is far superior to Comparative Example 2 (water absorption ratio 3.1, ammonia removal rate 66.8%) which only underwent delamination activation, Comparative Example 4 (water absorption ratio 3.5, ammonia removal rate 51.2%) which was directly modified without delamination, as well as commercially available bentonite cat litter (Comparative Example 5, ammonia removal rate 75.3%) and commercially available corn plant cat litter (Comparative Example 6, ammonia removal rate 73.5%). If only functional group modification is performed without delamination activation, the hydroxyl groups cannot be fully exposed, the amount of functional groups introduced is insufficient, and the deodorization performance cannot be effectively improved. This application also leverages the synergistic advantages of a multi-level porous structure to achieve a leap in overall performance: As the core amplification step of the triple modification, the microporous-mesoporous composite structure (specific surface area 173~223 m² / g, data from Examples 1-3) forms a synergistic effect of "basic-functional-scale-up" with the first two modification steps. Specific surface area is positively correlated with performance; for every 30~50 m² / g increase in specific surface area, the water absorption ratio can be increased by 0.8~1.2, and the ammonia removal rate can be increased by 5~8%. On the one hand, through the "capillary effect" of the pores and the synergistic effect of hydrophilic groups, "rapid water absorption + efficient water retention" is achieved, maintaining the water absorption ratio above 5.5. Compared with Comparative Example 3 (water absorption ratio 4.2, specific surface area 120 m² / g) of surface delamination + functional group modification, this is significantly improved. The improved water absorption rate (m² / g) of Comparative Example 4 (water absorption ratio 3.5, specific surface area 98 m² / g) without delamination is also superior to commercially available corn plant cat litter (Comparative Example 6, water absorption ratio 3.8). On the other hand, the large specific surface area increases odor adsorption sites, which, together with the deodorizing functions of amine and carboxyl groups, stabilizes the ammonia removal rate at over 98%. At the same time, the porous structure reduces particle shedding, further reduces dust, and allows moisture to diffuse evenly, causing the cat litter particles to form dense clumps with a clumping strength of 90.1~92.3%, which is far superior to Comparative Examples 1-4 and commercially available cat litter (Comparative Example 5 has a clumping strength of 93.0% but is not environmentally friendly, and the other comparative examples are all below 85%). This solves the pain point that a single modification step cannot take into account multiple performance aspects.

[0020] The environmentally friendly cat litter provided in this application has excellent environmental performance and realizes the resource utilization of waste: it uses agricultural husk waste such as rice husk and wheat husk as the only main raw material, without the addition of non-environmentally friendly components such as adhesives and synthetic polymers. In synergy with the triple modification process, the product can be naturally biodegraded, and the complete degradation time is only 45-48 days (data from Examples 1-3), which is far superior to unmodified rice husk cat litter (Comparative Example 1, 60 days), de-layered activated cat litter (Comparative Example 2, 55 days), direct modified cat litter without de-layering (Comparative Example 4, 58 days), and commercially available corn plant cat litter (Comparative Example 6, 58 days); commercially available bentonite cat litter (Comparative Example 5) is non-degradable and poses a risk of environmental pollution. Meanwhile, formaldehyde was not detected in the product, and the total mold count was only 48-52 CFU / g (data from Examples 1-3), which is far lower than 380 CFU / g in Comparative Example 1, 320 CFU / g in Comparative Example 2, 350 CFU / g in Comparative Example 4, and 280 CFU / g in Comparative Example 6. The heavy metal content meets the standards, there is no irritating odor, and it will not harm the health of cats. At the same time, it realizes the resource utilization of agricultural waste and reduces raw material costs. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially, including sodium hydroxide, hydrogen peroxide, ethylenediamine, and anhydrous ethanol (all analytical grade); silica template agent (white carbon black).

[0022] On one hand, the present invention provides a method for manufacturing environmentally friendly cat litter, comprising: The material is prepared by a triple synergistic modification process using natural rice husk biomass as raw material, including surface delamination activation, functional group modification, and multi-level porous structure construction. The triple synergistic modification process includes the following steps: S1 Surface Delamination and Activation: Remove the waxy and silica layers from the surface of natural rice husk biomass to expose the hydroxyl groups on cellulose and lignin, thus obtaining delamination and activated rice husks; S2 functional group modification: at least part of the hydroxyl groups of the delayered activated rice husk are converted into one or more of carboxyl and amino groups to obtain functional group modified rice husks; S3 Multi-level Porous Structure Construction: Modified rice husks were constructed by temperature-controlled carbonization to create a microporous-mesoporous composite structure.

[0023] The purpose of this invention is to provide an environmentally friendly cat litter and its manufacturing method and application. Using natural rice husks as raw materials, the invention achieves simultaneous improvement in the cat litter's water absorption, deodorization, dust reduction, and clumping strength through a triple synergistic modification process. This reduces production costs and makes the cat litter less prone to breakage during use, easier to clean, and biodegradable, thus meeting environmental protection requirements.

[0024] Raw material rice husks: Surface hydroxyl content (molar concentration) is 1.2~1.5 mmol / g; In step S1, after delamination and activation, the hydroxyl content (molar concentration) of the rice husk increases to 3.8~4.2 mmol / g (exposure rate >95%). In step S2, the hydroxyl groups of the delayered activated rice husk are converted into carboxyl groups, with a carboxyl group content (molar concentration) of 1.8~2.1 mmol / g and a conversion rate of 45%~52% for hydroxyl to carboxyl groups. Then, the resulting carboxylated rice husk is reacted with ethylenediamine to introduce amino groups, with an amino group content (molar concentration) of 1.2~1.5 mmol / g and an amino group conversion rate of 30%~38% based on the total amount of remaining hydroxyl and carboxyl groups in the carboxylated rice husk. The total active group (carboxyl and amine) content (molar concentration) is 3.0~3.6 mmol / g.

[0025] Methods for determining functional group content In this invention, the hydroxyl, carboxyl, and amino group contents of raw rice husks, de-layered activated rice husks, functional group modified rice husks, and final modified rice husks were determined using the following methods. All samples were dried to constant weight at 105°C before measurement.

[0026] 1. Determination of hydroxyl content (acylation titration method) Referring to GB / T7383-2007 and the general method for the determination of hydroxyl groups in lignocellulose materials, the 4-dimethylaminopyridine-catalyzed acetic anhydride acylation method was adopted.

[0027] Measurement steps: Accurately weigh approximately 0.5 g of the dried sample (accurate to 0.0001 g) and place it in a stoppered conical flask. Add 10 mL of acylation reagent (prepared from acetic anhydride and pyridine at a volume ratio of 1:4, containing 0.1 g / L 4-dimethylaminopyridine as a catalyst), seal the flask, and incubate at 45 °C with shaking for 15 min. Then add 5 mL of deionized water for hydrolysis for 20 min. After cooling to room temperature, add 30 mL of isopropanol and perform potentiometric titration with 0.1 mol / L sodium hydroxide standard solution, recording the titration endpoint volume V1. Simultaneously perform a blank experiment (without sample), recording the blank titration volume V0. The hydroxyl content is calculated using the following formula: Q OH =(V0-V1)×c / m In the formula: Q OH -Hydroxy content, in mmol / g; V0 - Volume of sodium hydroxide standard solution consumed in blank titration, in mL; V1 - The volume of sodium hydroxide standard solution consumed in the sample titration, in mL; The concentration of c-sodium hydroxide standard solution is expressed in mol / L; m - Sample mass, in grams.

[0028] 2. Determination of carboxyl content (conductometric titration) Refer to the Boehm titration method and the standard operating procedures for the carboxyl conductivity titration of lignocellulose.

[0029] Measurement steps: Accurately weigh approximately 0.3 g (accurate to 0.0001 g) of the dried sample and place it in a 150 mL beaker. Add 50 mL of 0.01 mol / L sodium chloride solution and disperse magnetically for 10 min. Titrate with 0.01 mol / L sodium hydroxide standard solution at a rate of 0.2 mL / min, and record the change in solution conductivity. Plot a conductivity-titer volume curve. The volume difference between the two inflection points on the curve represents the volume of alkali solution consumed by the carboxyl groups. The carboxyl content is calculated using the following formula: Q COOH =V NaOH ×c / m In the formula: Q COOH - Carboxyl group content, in mmol / g; V NaOH -The carboxyl group corresponds to the volume of sodium hydroxide standard solution consumed between the inflection points, in mL; c-Concentration of sodium hydroxide standard solution, in mol / L; m - Sample mass, in grams.

[0030] 3. Determination of amine content (Kjeldahl method - indirect calculation) The amine content was calculated by measuring the total nitrogen content of the sample, assuming that all nitrogen atoms exist in the form of free amine groups (-NH2) (it has been verified that there are no other nitrogen-containing byproducts in this modification process).

[0031] Measurement steps: Accurately weigh approximately 0.2 g of the dried sample (accurate to 0.0001 g) and digest it using a Kjeldahl nitrogen analyzer: add 5 mL of concentrated sulfuric acid (98%) and 0.5 g of a copper sulfate / potassium sulfate mixed catalyst (mass ratio 1:10), and digest at 420 °C for 1.5 h until the solution is clear and transparent. After cooling, distill and titrate using a fully automated Kjeldahl nitrogen analyzer, absorbing with boric acid absorption solution and titrating with 0.01 mol / L hydrochloric acid standard solution. The total nitrogen content is calculated using the following formula: N total =V HCl ×c×14.01 / m In the formula: N total - Total nitrogen content, in mg / g; V HCl - The volume of standard hydrochloric acid solution consumed in the titration is in mL; c-Concentration of hydrochloric acid standard solution, in mol / L; m - Sample mass, in grams; 14.01 - Molar mass of nitrogen, in g / mol.

[0032] The amino group content is calculated using the following formula: Q NH2 =N total / 14.01 In the formula: Q NH2 - Amine content, in mmol / g.

[0033] 4. Total content of active groups The total active group content is the sum of the carboxyl group and the amino group content: Q total =Q COOH +Q NH2 (mmol / g) Note: The hydroxyl group conversion rate and amino group grafting rate are calculated by comparing the changes in the corresponding functional groups before and after the reaction.

[0034] Preferably, step S1 includes the following steps: S101 Take natural rice husk biomass, add an alkaline solution with a mass fraction of 5-10%, the material-to-liquid ratio is 1:8-12 (g / mL), heat to 70-90℃ and stir for 1.5-2.5 hours; After the S102 reaction is complete, the solution is repeatedly filtered and washed with deionized water until the pH of the filtrate is 6.5–7.5. S103 The washed product is placed in a ball mill and ball-milled at a speed of 180-220 r / min for 20-40 min, and then dried until the moisture content is ≤8% to obtain de-layered activated rice husk.

[0035] Preferably, the alkaline solution is either a sodium hydroxide solution or a potassium hydroxide solution.

[0036] Preferably, step S2 includes the following steps: S201 involves adding de-layered and activated rice husks to a 3-6% hydrogen peroxide solution at a material-to-liquid ratio of 1:4-6 (g / mL), heating to 65-75℃ for 1-2 hours of oxidation reaction, with continuous stirring during the process to introduce carboxyl groups. After S202 oxidation is completed, filter and dry the product, then add 2-4% ethylenediamine solution at a material-to-liquid ratio of 1:2-4 (g / mL), heat to 75-85℃ and react for 0.5-1.5 h to introduce amine groups; After the S203 reaction is completed, filter the mixture, wash it 2-3 times with anhydrous ethanol, and dry it until the moisture content is ≤8% to obtain functional group modified rice husk.

[0037] Preferably, in step S3, the temperature-controlled carbonization includes the following steps: The functional group-modified rice husks were placed in an inert gas atmosphere with an inert gas introduction rate of 0.5~1L / min, and heated to 200~600℃ at a heating rate of 4~6℃ / min. The mixture was then carbonized at a constant temperature for 1~2h to obtain modified rice husks with a microporous-mesoporous composite structure. The inert gas was either nitrogen or argon.

[0038] Preferably, the molar concentration of the carboxyl group introduced in step S201 is 1.5~2.5 mmol / g; The molar concentration of the amine group introduced in step S202 is 1.0~2.0 mmol / g.

[0039] Preferably, the manufacturing method of the environmentally friendly cat litter further includes step S4 molding process: after the modified rice husks are crushed, sieved, and pressed into shape, the environmentally friendly cat litter product is obtained. In step S4, the particle size of the modified rice husk after crushing and sieving is 1.5~3.0mm, the pressing pressure is 1.5~2.5MPa, and the molding time is 8~12s.

[0040] Preferably, the natural grain husk biomass includes any one or more of rice husks, wheat husks, sorghum husks, and millet husks.

[0041] On the other hand, the present invention provides an environmentally friendly cat litter, which is manufactured according to the manufacturing method of environmentally friendly cat litter as described in any of the preceding claims, wherein the environmentally friendly cat litter has a microporous-mesoporous composite structure and a specific surface area ≥173m² / g.

[0042] In another aspect, the present invention provides an application of the environmentally friendly cat litter as described in any of the preceding claims in the treatment of feline excrement.

[0043] Example 1 Raw material: Rice husks (crushed to 1.5~3.0mm and dried to moisture content ≤8%).

[0044] This embodiment provides a method for manufacturing environmentally friendly cat litter, including the following steps: S1 Surface Delamination and Activation: Take 100g of dried rice husks, add 1000mL of 8% sodium hydroxide solution (material-to-liquid ratio 1:10g / mL), heat to 80℃ and stir in a constant temperature water bath for 2h, stirring once every 30min; after the reaction, wash with deionized water until the pH of the filtrate is 6.5; put the product into a ball mill, ball mill at 200r / min for 30min, and dry until the moisture content is ≤8% to obtain delamination and activated rice husks; S2 functional group modification: Delayered activated rice husks were added to 500 mL of 5% hydrogen peroxide solution (solid-liquid ratio 1:5 g / mL), heated to 70℃ and reacted in a constant temperature water bath for 1.5 h with continuous stirring; after filtration and drying, 300 mL of 3% ethylenediamine solution (solid-liquid ratio 1:3 g / mL) was added, heated to 80℃ and reacted in a constant temperature water bath for 1 h; after filtration, the mixture was washed twice with anhydrous ethanol and dried until the moisture content was ≤8% to obtain functional group modified rice husks; Construction of S3 hierarchical porous structure: Functional group modified rice husk was placed in a muffle furnace, nitrogen was introduced at a rate of 0.5 L / min, the temperature was increased to 350℃ at a rate of 5℃ / min, and carbonized at a constant temperature for 1.5 h to obtain modified rice husk with microporous-mesoporous composite structure. S4 molding process: Modified rice husks are crushed and sieved to 1.5~3.0mm, and then pressed into shape under 2MPa pressure for 10s to obtain environmentally friendly cat litter.

[0045] Example 2 Raw material: Wheat hulls (crushed to 1.5~3.0mm and dried to moisture content ≤8%).

[0046] This embodiment provides a method for manufacturing environmentally friendly cat litter, including the following steps: S1 Surface Delamination and Activation: Take 100g of dried wheat husks, add 900mL of 10% potassium hydroxide solution (material-liquid ratio 1:9 g / mL), heat to 75℃ and stir in a constant temperature water bath for 2.5h; wash until pH=7.0, ball mill at 180r / min for 40min, and dry until moisture content ≤8% to obtain delamination and activated rice husks; S2 functional group modification: Add 400 mL of 6% hydrogen peroxide solution (solid-liquid ratio 1:4 g / mL), heat to 65℃ for 2 h of oxidation reaction; filter and dry, then add 250 mL of 4% ethylenediamine solution (solid-liquid ratio 1:2.5 g / mL), heat to 85℃ for 0.5 h of reaction; wash 3 times with anhydrous ethanol, and dry to moisture content ≤8% to obtain functional group modified rice husk; Construction of S3 hierarchical porous structure: Argon gas was introduced at a rate of 1 L / min, the temperature was increased to 600℃ at a rate of 4℃ / min, and carbonized at a constant temperature for 1 h to obtain modified rice husk with microporous-mesoporous composite structure. S4 molding process: crush and sieve to 1.5~3.0mm, molded under 2.5MPa pressure for 8s to obtain environmentally friendly cat litter.

[0047] Example 3 Raw materials: rice husks: wheat husks = 1:1 (mass ratio), crushed to 1.5~3.0mm, and dried to moisture content ≤8%.

[0048] This embodiment provides a method for manufacturing environmentally friendly cat litter, including the following steps: S1 Surface Delamination and Activation: Take 100g of mixed rice husks, add 1200mL of 5% sodium hydroxide solution (material-liquid ratio 1:12 g / mL), heat to 90℃ and react for 1.5h; wash until pH=7.5, ball mill at 220r / min for 20min, and dry until moisture content ≤8% to obtain delamination and activated rice husks; S2 functional group modification: Add 600 mL of 3% hydrogen peroxide solution (solid-liquid ratio 1:6 g / mL), heat to 75℃ and oxidize for 1 h; filter and dry, then add 400 mL of 2% ethylenediamine solution (solid-liquid ratio 1:4 g / mL), heat to 75℃ and react for 1.5 h; wash twice with anhydrous ethanol, and dry to moisture content ≤8% to obtain functional group modified rice husk; Construction of S3 hierarchical porous structure: Functional group modified rice husks were placed in a muffle furnace, nitrogen was introduced at a rate of 0.8 L / min, the temperature was increased to 200℃ at a rate of 6℃ / min, and carbonized at a constant temperature for 2 hours to obtain modified rice husks with microporous-mesoporous composite structure. S4 molding process: crush and sieve to 1.5~3.0mm, molded under 1.5MPa pressure for 12s to obtain environmentally friendly cat litter.

[0049] Comparative Example 1 The manufacturing method of the environmentally friendly cat litter provided in Comparative Example 1 includes the following steps: Rice husks were crushed to 1.5~3.0mm, dried to a moisture content of ≤8%, and directly pressed into shape at 2MPa for 10s without any modification treatment.

[0050] Comparative Example 2 The manufacturing method of the environmentally friendly cat litter provided in Comparative Example 2 includes the following steps: The technical solution of Comparative Example 2 is the same as that of Example 1, except that after rice husks are processed according to step S1 of Example 1, they are directly pressed and shaped in step S4 of Example 1 without functional group modification and multi-level porous structure construction.

[0051] Comparative Example 3 The manufacturing method of the environmentally friendly cat litter provided in Comparative Example 3 includes the following steps: The technical solution of Comparative Example 3 is the same as that of Example 1, except that after the rice husks are processed according to the S1 and S2 steps of Example 1, they are directly pressed and shaped in step S4 of Example 1 without the construction of a multi-level porous structure.

[0052] Comparative Example 4 The manufacturing method of the environmentally friendly cat litter provided in Comparative Example 4 includes the following steps: The technical solution of Comparative Example 4 is the same as that of Example 1, except that the rice husks are crushed to 1.5~3.0mm and dried to a moisture content of ≤8%. The surface de-lamination and activation treatment in step S1 of Example 1 is not performed. Instead, the S2, S3 and S4 steps of Example 1 are performed directly to obtain the finished product.

[0053] Comparative Example 5 For comparison example 5, commercially available mainstream bentonite cat litter was directly purchased without any processing and its performance was directly tested.

[0054] Comparative Example 6 Comparative Example 6 provides commercially available mainstream pure corn plant-based cat litter, which uses corn cob as the main raw material and does not contain bentonite or mineral components. It is a commercially available, qualified product, which is purchased directly without any processing and then directly subjected to performance testing.

[0055] Experimental preparation and performance testing standards 1. Experimental equipment: ball mill, constant temperature water bath, muffle furnace with inert gas protection device, electronic balance (accuracy 0.001g), digital display thrust gauge (accuracy 0.01N), dust collection device, BET specific surface area analyzer, Nessler's reagent spectrophotometer (compliant with HJ533 standard), electric thermostatic drying oven, atomic absorption spectrometer (compliant with GB / T 13080 standard), powder tablet press, polytetrafluoroethylene corrosion-resistant container, corrosion-resistant protective gloves / goggles.

[0056] 2. Performance testing standards: (1) Specific surface area: The BET nitrogen adsorption method was used, and the test conditions were 77K, degassing temperature 105℃, and degassing time 3h. (2) Water absorption ratio: In accordance with T / ZGXX 0005 "Pet Cleaning and Hygiene Products Cat Litter", at 25℃ and 60% relative humidity, 10g of cat litter was soaked in deionized water for 10 minutes and then filtered. The weight after water absorption / initial weight was calculated. (3) Clump strength: In accordance with T / ZGXX 0005, the cat litter absorbs 3 times its own weight of physiological saline and naturally forms a clumping structure. The clumping strength is characterized by the breakage rate (the lower the breakage rate, the higher the clumping strength). At the same time, the clumping height and clumping weight are measured. (4) Dust content: Refer to T / SDPIA05 "General Technical Specifications for Pet Cat Litter". 100g of cat litter is dropped freely from a height of 1m. After collecting and drying the dust, calculate the dust mass / initial cat litter mass × 100%. (5) Ammonia removal rate: Follow T / ZGXX0005 and HJ533. Add 5g of cat litter to 50mL of ammonia nitrogen simulated excrement solution, shake at 25℃ for 1h, and measure the ammonia nitrogen concentration before and after adsorption to calculate the removal rate. (6) Environmental protection indicators: formaldehyde emission shall be in accordance with T / ZGXX 0005; total mold count shall be in accordance with TB / T13092, and the culture conditions shall be 28±2℃ for 48h; aflatoxin B1 shall be in accordance with NY / T2071; lead content shall be in accordance with GB / T13080. (7) Biodegradability: The cat litter was placed in a natural soil environment with a pH of 6.5-7.5 (temperature 25±2℃, humidity 60±5%), and the time for complete degradation (no obvious solid residue) was recorded periodically. The performance of each example and comparative example was tested according to the performance testing standard, and the results are shown in Table 1. All data are the average of three parallel experiments. Table 1 Summary of Performance Test Results

[0057] 2. Results Analysis (1) Necessity of triple synergistic modification: As can be seen from the comparison between Examples 1-3 and Comparative Examples 1-4, the unmodified Comparative Example 1 has the worst performance in all aspects, with high dust content and poor water absorption and deodorization performance, proving that natural rice husks need to be modified to meet the needs of cat litter use; Comparative Example 2, which only has surface de-layer activation, has a certain improvement in performance, but lacks hydrophilic functional groups and porous structure, and its water absorption and deodorization performance still do not meet expectations; Comparative Example 3, which has surface de-layer + functional group modification, has further improved performance, but its specific surface area is insufficient, and its water absorption and deodorization performance still have a gap; Comparative Example 4, which is directly modified without de-layer (ammonia removal rate is only 51.2%, water absorption ratio is 3.5, dust content is 0.85%), cannot fully expose hydroxyl groups because the wax layer and silica layer on the surface of the rice husk are not removed, and the functional group modification and hierarchical pore construction cannot play a role, and its performance is far lower than that of Examples 1-3, further proving that surface de-layer activation is the basis for subsequent modification, and all three are indispensable. Examples 1-3, which underwent triple synergistic modification, achieved a qualitative leap in all aspects of performance, proving that the synergistic effect of surface delamination activation, functional group modification, and multi-level porous structure construction has improved the overall performance of cat litter.

[0058] (2) Comparative advantages of the present invention with commercially available cat litter: Compared with commercially available bentonite cat litter (Comparative Example 5), the present invention has extremely low dust content, better deodorization performance, and is completely biodegradable with no environmental hazards, thus solving the environmental pain point of bentonite cat litter; Compared with commercially available corn plant cat litter (Comparative Example 6), the present invention is significantly better than the other in terms of water absorption, clumping, deodorization, and dust reduction, with a shorter degradation time and better overall performance.

[0059] (3) Applicability of the process: In Examples 1-3, rice husks, wheat husks and rice husks + wheat husks were used as raw materials, and multi-level pores were constructed by temperature-controlled carbonization or template method. All of them achieved excellent performance, which proves that the manufacturing method of the present invention is applicable to a variety of natural grain husk biomass. Both multi-level pore construction methods can be flexibly applied. The process is highly controllable, does not require complex equipment, and is convenient for industrial production.

[0060] Taking Example 1 as an example, the functional group content of the products at each stage of the preparation process was determined using the functional group content determination method described above, and the results are shown in Table 2 below: Table 2. Experimental data on the functional group content of the products at each stage of the preparation process in Example 1.

[0061] Using the above method for determining the functional group content, the conversion rate of hydroxyl groups to carboxyl groups is approximately 50%, and the conversion rate of amino groups (based on the total amount of carboxyl groups and remaining hydroxyl groups) is approximately 35%.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for manufacturing environmentally friendly cat litter, characterized in that, include: The material is prepared by a triple synergistic modification process using natural rice husk biomass as raw material, including surface delamination activation, functional group modification, and multi-level porous structure construction. The triple synergistic modification process includes the following steps: S1 Surface Delamination and Activation: Remove the waxy and silica layers from the surface of natural rice husk biomass to expose the hydroxyl groups on cellulose and lignin, thus obtaining delamination and activated rice husks; S2 functional group modification: at least part of the hydroxyl groups of the delayered activated rice husk are converted into one or more of carboxyl and amino groups to obtain functional group modified rice husks; S3 Multi-level Porous Structure Construction: Modified rice husks were constructed by temperature-controlled carbonization to create a microporous-mesoporous composite structure.

2. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, Step S1 includes the following steps: S101 Take natural rice husk biomass, add an alkaline solution with a mass fraction of 5-10%, the material-to-liquid ratio is 1:8-12 (g / mL), heat to 70-90℃ and stir for 1.5-2.5 hours; After the S102 reaction is complete, the solution is repeatedly filtered and washed with deionized water until the pH of the filtrate is 6.5–7.

5. S103 The washed product is placed in a ball mill and ball-milled at a speed of 180-220 r / min for 20-40 min, and then dried until the moisture content is ≤8% to obtain de-layered activated rice husk.

3. The method for manufacturing environmentally friendly cat litter according to claim 2, characterized in that, The alkaline solution is either a sodium hydroxide solution or a potassium hydroxide solution.

4. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, Step S2 includes the following steps: S201 involves adding de-layered and activated rice husks to a 3-6% hydrogen peroxide solution at a material-to-liquid ratio of 1:4-6 (g / mL), heating to 65-75℃ for 1-2 hours of oxidation reaction, with continuous stirring during the process to introduce carboxyl groups. After S202 oxidation is completed, filter and dry the product, then add 2-4% ethylenediamine solution at a material-to-liquid ratio of 1:2-4 (g / mL), heat to 75-85℃ and react for 0.5-1.5 h to introduce amine groups; After the S203 reaction is completed, filter the mixture, wash it 2-3 times with anhydrous ethanol, and dry it until the moisture content is ≤8% to obtain functional group modified rice husk.

5. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, The molar concentration of the carboxyl group introduced in step S201 is 1.5~2.5 mmol / g; The molar concentration of the amine group introduced in step S202 is 1.0~2.0 mmol / g.

6. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, In step S3, the temperature-controlled carbonization includes the following steps: The functional group-modified rice husks were placed in an inert gas atmosphere and heated to 200-600℃ at a heating rate of 4-6℃ / min, and carbonized at a constant temperature for 1-2 hours to obtain modified rice husks with a microporous-mesoporous composite structure; the inert gas was either nitrogen or argon.

7. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, The manufacturing method of the environmentally friendly cat litter also includes step S4 molding process: after the modified rice husks are crushed, screened and pressed into shape, the environmentally friendly cat litter product is obtained. In step S4, the particle size of the modified rice husk after crushing and sieving is 1.5~3.0mm, the pressing pressure is 1.5~2.5MPa, and the molding time is 8~12s.

8. The method for manufacturing environmentally friendly cat litter according to claim 1, characterized in that, The natural grain husk biomass includes any one or more of the following: rice husks, wheat husks, sorghum husks, and millet husks.

9. An environmentally friendly cat litter, characterized in that, The environmentally friendly cat litter is manufactured according to the manufacturing method of any one of claims 1-8, and the environmentally friendly cat litter has a microporous-mesoporous composite structure with a specific surface area ≥173m² / g.

10. The application of the environmentally friendly cat litter as described in claim 9 in the treatment of feline excrement.